Degradation mechanism of La0.6Sr0.4Co0.2Fe0.8O3-δ/Gd0.1Ce0.9O2-δ composite electrode operated under solid oxide electrolysis and fuel cell conditions. (1st July 2017) - Laurencin, J.; Hubert, M.; Sanchez, D. Ferreira; Pylypko, S.; Morales, M.; Morata, A.; Morel, B.; Montinaro, D.; Lefebvre-Joud, F.; Siebert, E.
Abstract: A set of long-term tests (t ≥ 1000 h) have been carried out in fuel cell and electrolysis modes on typical Ni-YSZ//YSZ//LSCF-CGO cells. The degradation rates were found to be higher in electrolysis than in fuel cell operation. Post-test analyses have revealed that Sr diffusion and formation of SrZrO3 at YSZ/CGO interface occur mainly during electrolysis operation, whereas the process is very limited in fuel cell mode. As a consequence, LSCF destabilization is found to be not involved in the degradation of cell performances during fuel cell operation while it could explain the highest degradation rates recorded in electrolysis mode. An in-house multi-scale model has been used to interpret the role of the cell operating mode on the LSCF demixing mechanism. The simulations have shown that the electrolysis operation leads to a strong depletion of oxygen vacancies in LSCF material (while the fuel cell condition results in an increase in the concentration of oxygen vacancies). It has been proposed that the depletion in oxygen vacancies under electrolysis polarization could drive the Sr release from the structure, and in turn, could explain the experimental results. Based on this proposition, a possible mechanism for the LSCF destabilization and SrZrO3 formation is detailed.